Melodramatic formations : American theatre and society, 1820-1870 - McConachie, Bruce A. (Studies in theatre history and culture., 1992)
The middle years of the nineteenth century were a time of dynamic artistic and social changes in America. Now, Melodramatic Formations is the first study to trace these changes in popular stage melodrama's production, dramatic form, and audience reception. Bruce McConachie shows how the theatrical mutability that characterized the years 1820 to 1870 is inextricably tied to the decline of elite paternalism and republicanism and the rise of bourgeois rationalism and respectability. Taking a rigorous interdisciplinary approach, McConachie examines several historical regularities of production, ge.